Recovery from Sexual Compulsivity. Issue 3 (3rd July 2017) - Schwartz, Mark F.; Southern, Stephen
ABSTRACT: Sexual compulsivity is a developmental adaptation to neglect or abuse that leads to cognitive, behavioral, and emotional consequences as well as impairment in capacity for intimacy. Recovery from sexual compulsivity involves integration of various psychotherapy components needed to address underlying trauma, repetition compulsion, developmental roadblocks, compulsive behavioral reenactments, emotion dysregulation, and intimacy disorder. Effective treatment involves trauma work, symptom-specific treatment, and reconstruction of an erotic template or love map that reduces objectification, compulsion, and variance while affording opportunities for corrective emotional experience, skills development, and enhancement of choices for intimacy.